(untitled) (Journal of Ideas in Health, 2024)
Background: Korsakoff’s syndrome (KS) is a debilitating psychoneurological disorder that can occur in adults with alcohol use disorder (AUD). People with KS experience a sudden onset of symptoms including confabulation, anterograde and retrograde amnesias, apathy, issues with vision and gait, and lack of insight. Frequently an adult child of the parent with alcohol-induced KS becomes the caregiver, regardless of the status or quality of the relationship with their parent. While there is a rich literature base in the areas of adult children of parents with AUD and caregiving, there are no studies that have explored the experiences of adult children caring for a parent with alcohol-induced KS. This study aimed to explore the experiences of adult children who provide care for a parent or parental figure suffering from alcohol-induced Korsakoff syndrome (KS). Method: This study used a generic qualitative approach with thematic analysis using both in person and web-based video interview methods and field notes to address this gap in the literature. Eight individuals participated in the study, men (n=2) and women (n=6), with participants ranging in age from 31 to 43 years (average age 37 years). Results: Five themes emerged: addiction and the adult child, experiencing caregiver burden, experiencing a variety of emotions, professional healthcare experiences, and observations of symptoms. These themes emerged over seven anchor events in their caregiving experiences: interactions with their parent pre-diagnosis, parent’s medical emergency, hospitalization, diagnosis, housing, legal, and financial. Conclusion: The results provide a foundation for future research in the areas of KS, caregiving, and adult children of parents with AUD. They also provide a basis to inform the development of interventions with this population and demonstrate a need for more awareness of KS among healthcare professionals.